Osthole Suppresses Knee Osteoarthritis Development by Enhancing Autophagy Activated via the AMPK/ULK1 Pathway - Teng Ma; Xiangpeng Wang; Wenjing Qu; Lingsen Yang; Cheng Jing; Bingrui Zhu; Yongkui Zhang; Wenpeng Xie (Molecules, 2022)
Knee osteoarthritis (KOA) is an increasingly prevalent heterogeneous disease characterized by cartilage erosion and inflammation. As the main chemical constituent of Angelicae Pubescentis Radix (APR), an anti-inflammatory herbal medicine, the potential biological effects and underlying mechanism of osthole on chondrocytes and KOA progression remain elusive. In this study, the potential effect and mechanism of osthole on KOA were investigated in vitro and in vivo. We found that osthole inhibited IL-1β-induced apoptosis and cartilage matrix degeneration by activating autophagy in rat chondrocytes. In addition, osthole could activate autophagy through phosphorylation of AMPK/ULK1, and AMPK serves as a positive upstream regulator of ULK1. Furthermore, KOA rats treated with osthole showed phosphorylation of the AMPK/ULK1 pathway and autophagy activation, as well as cartilage protection. Collectively, the AMPK/ULK1 signaling pathway can be activated by osthole to enhance autophagy, thereby suppressing KOA development. Osthole may be a novel and effective therapeutic agent for the clinical treatment of KOA.